The Association between Pain, Radiographic Severity, and Centrally-mediated Symptoms in Women with Knee Osteoarthritis - Murphy, Susan L. (2011)
OBJECTIVE: To examine the relationship between pain, radiographic severity, and a common set of co-occurring centrally-mediated symptoms in women with knee osteoarthritis. METHODS: Participants underwent knee radiographs, and had repeated assessments of pain severity and other centrally-mediated symptoms, such as fatigue, sleep quality, and depression, during a five day home monitoring period. To examine associations between pain severity (the average of pain over the home monitoring period), measures of osteoarthritis radiographic severity (Kellgren Lawrence grade, minimum joint space width), centrally-mediated symptoms, and demographics (age) were used. Symptoms of fatigue, depression, and sleep efficiency were used in a composite measure representing centrally-mediated symptoms. RESULTS: Using a series of linear regression models in which each variable was entered hierarchically (N = 54), the final model showed 27% of the variance in pain severity was explained by age, radiographic severity, and centrally-mediated symptoms. Centrally-mediated symptoms explained an additional 10% of the variance in pain severity after the other two variables were entered. CONCLUSIONS: Both radiographic severity and centrally-mediated symptoms were independently and significantly associated with pain severity in women with knee osteoarthritis. In addition to more severe radiographic features, women with higher centrally-mediated symptoms had greater pain severity. Treatments for women with symptomatic knee osteoarthritis may be optimized by addressing both peripheral and central sources of pain.